A Theoretical Study on the Thermoelectric Properties of Porous Armchair Germanene Nanoribbons - Kaur, Varunpreet; Kaur Randhawa, Deep Kamal; Kaur, Sukhdeep (Asian Journal of Electrical Sciences, 2019)
Since the limits of conventional sources of energy are rapidly approaching, the thermoelectric devices have attracted attention for their potential of power generation directly from waste heat. In this paper, thermoelectric properties of porous armchair Germanene nanoribbons (AGeNRs) have been explored for a range of pore dimensions in order to achieve a high performance two-dimensional nanoscale thermoelectric device. The work has been done to investigate the influence of different nanopore shapes and their associated positions on the thermoelectric performance so as to tune it to the optimum pore shape and position that would enhance the overall thermoelectric efficiency. Also, the effect of passivation of the pore edges on thermoelectric parameters for all shapes has been studied. Further, the influence of temperature dependence on figure of merit has been observed. Ballistic transport regime and semi-empirical method using Huckel basis set is used to obtain the electrical properties while the Brenner potential is used for the phononic properties.